Consideraciones de seguridad en la prescripción de medicamentos antiinflamatorios no esteroideos (AINEs), a través de una revisión de revisiones sistemáticas - Olry de Labry Lima, A.; Salamanca-Fernández, E.; Alegre del Rey, E.J.; Matas Hoces, A.; González Vera, M.Á.; Bermúdez Tamayo, C. (Anales del Sistema Sanitario de Navarra, 2021)
Non-steroidal anti-inflammatory drugs (NSAIDs) are among the most widely used drugs worldwide. This makes it necessary to carry out a comprehensive synthesis of the available evidence on the safe and adequate prescription of NSAIDs in patients with cardiovascular disease, chronic kidney disease, hypertension, heart failure or liver cirrhosis and in general population. For this, a review of systematic reviews was carried out. Data extraction and analysis were performed independently by two reviewers and a narrative synthesis of the results was carried out. The use of NSAIDs is associated with a significantly higher probability of hepatotoxicity and kidney damage, as well as increased risk of exacerbation of heart failure. Taking into account the increased cardiovascular, liver and kidney risk, the prescription of NSAIDs should be carried out with caution, considering the treatment duration and the patient’s situation. For this reason, patients should be informed about their possible health consequences as well as ensuring adequate monitoring of them.